Perception of the multi-professional team regarding the safety of pediatric patients in critical areas - Fernanda Stroeher Pereira; Marina Scherer Silveira; Letícia Maria Hoffmann; Merianny de Ávila Peres; Márcia Koja Breigeiron; Wiliam Wegner (Universidade Federal de Santa Maria, 2021)
Objective: to know the perception of the multi-professional team regarding the strategies for the safety of pediatric patients in critical areas. Method: a qualitative and exploratory-descriptive study carried out in pediatric intensive care and emergency units of three hospitals in the city of Porto Alegre, between November 2018 and March 2019, linked to the matrix project entitled "Patient safety in hospital care services for children and adolescents in the city of Porto Alegre". A total of 20 practitioners who worked in these areas and who had experience in pediatrics for at least one year were included. Five collective interviews were conducted, which were audio-recorded and later transcribed for content analysis. Results: three categories arose: Maintenance of adherence to the protocols/goals of pediatric patient safety, Teaching/education in patient safety, and Involvement of companions for the promotion of patient safety. Conclusion: the practitioners acknowledge that the strategies described demonstrate minimal conditions to reach care quality and incident prevention, essential for patient safety.